Pelatihan Pembuatan dan Penggunaan Pupuk Organik Cair dari Urine Sapi untuk Tanaman Hortikultura di Desa Sukadana, Kecamatan Pujut, Kabupaten Lombok Tengah - Beni Nungroho Sudiantoro; Adelia Adelia; Devia Arisanti; Ilham Ilham; Arzaki Zaget Oasis; M. Afdhol Gilman; Munawara Putia; Aenan Salsabila; Ida Rohani; Anisa Agustina; I Gede Adhitya Wisnu Wardhana (Sinergi dan Harmoni Masyarakat MIPA, 2025)
The Community Service Program for Village Empowerment (KKN-PMD) at the University of Mataram (UNRAM) was conducted on January 16, 2024, in Sukadana Village, Pujut District, Central Lombok Regency, to empower farmers in utilizing livestock waste as liquid organic fertilizer (POC) from cow urine. This initiative aims to enhance soil fertility, reduce dependence on chemical fertilizers, and promote sustainable agriculture. Additionally, the use of livestock waste for POC production is expected to minimize environmental pollution caused by unmanaged cow urine disposal. Using the Participatory Action Research (PAR) approach, the program engaged farmers in training and hands-on practice to produce POC using cow urine, EM4, and molasses. The results showed that POC improved soil fertility, restored soil structure, and increased agricultural yields by 15–20% while reducing production costs. Beyond economic benefits, this program encourages farmers to adopt environmentally friendly agricultural practices and introduces a more sustainable fertilizer alternative. The improved knowledge and skills in waste management are expected to have a lasting positive impact on sustainable farming in Sukadana Village and serve as a model for other regions with similar agricultural conditions.